L2 translation in Brazil: Results of a survey - Atkinson, Rebecca (The Journal of Specialised Translation, 2023)
This study reports on an online survey conducted in Brazil with the aim of identifying the prevalence of L2 translation in the country and some of the characteristics and practices of the professionals engaged in it, focusing on translation into English. 522 valid responses were received from professionals living in Brazil (95%) and abroad (5%). 78% of the respondents whose L1 was Portuguese reported translating into other languages: 53% only into English and 11% into English and another language. 60% of the 326 respondents who translated into English did so 50% or more of the time. L2 translation of all types was reported, including audiovisual and literary. Only 27% of the respondents who did L2 translation into English always had their translations revised by a third party, and just 21% worked with a native English proofreader. 52% of the respondents who did L2 translations into English had done no training in Portuguese-English translation. High social media usage and interest in short L2 translation courses were identified, suggesting that video e-learning could be exploited for L2 translation training. Trainers and course designers should consider altering the proportion and content of practical training offered in L2 translation to reflect market demands.